Eletrodeposição de filmes finos de CdTe sobre substrato de Pt para uso em sistemas fotovoltaicos - Magalhães, Rafael Aragão (2012)
This work presents the investigation on the voltammetrc deposition of cadmium telluride (CdTe) onto platinum substrate from sulfuric acid-based electrolyte, at room temperature (24 °C). For this purpose, the linear sweep voltammetry technique was used in order to establish the values of deposition potential (-167 up to -444mV). The data extracted from the voltammetric essays suggest that different chemical and electrochemical steps are involved. The formation of cathodic peak with subsequent formation of the current plateau indicates the existence of mixed control of the CdTe deposition, while the anodic peak points out that the anodic dissolution of the material is complete. The deposited film presents dark gray color and its tonality depends on the potential. The films were characterized by scanning electron microscopy (SEM) and X-rays diffraction (XRD) techniques. It was found that the films deposited at different potentials have similar morphology, as like grains, are uniform and compact. The crystallite size is influenced by the potential. The XRD patterns of deposited films show peaks associated with the (200), (220), (311), (421) and (422) planes.